Thermohydraulic modeling in transient state for evaluation of pipeline shutdown and restart procedures - Nieto-Londoño, César; Bustamante-Chaverra, Carlos Andrés; Buendía-García, Jhon Anderson; Novoa , Luz Angela; García-Lázaro, Joao Alexander; Viviescas-Ibarra, Geoffrey (CT&F - Ciencia, Tecnología y Futuro, 2019)
In order to study shutdown and re-start in heavy crude oil pipelines, a model was developed. It simulates, in a transient state, the behavior of pressure, flow and temperature variables, averaged over the cross-sectional area and as a function of time and the axial coordinate. The model was validated with actual operational data from a test case. Results obtained for different operating points, stopping time, crude properties, topographies and lengths are presented. Additionally, the governing equations are converted to dimensionless expressions in order to obtain the dimensionless numbers relevant to the re-start operation for crude oil pipelines.